2016
DOI: 10.12659/msm.895758
|View full text |Cite
|
Sign up to set email alerts
|

Utility of MRI Diffusion Tensor Imaging in Carpal Tunnel Syndrome: A Meta-Analysis

Abstract: BackgroundAfter successful utilization of diffusion tensor imaging (DTI) in detecting brain pathologies, it is now being examined for use in the detection of peripheral neuropathies. The aim of this meta-analysis was to evaluate the diagnostic potentials of DTI in carpal tunnel syndrome (CTS).Material/MethodsThe literature search was performed in multiple electronic databases using a keyword search and final selection of the studies was based on predetermined inclusion and exclusion criteria. We performed a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 48 publications
3
19
0
Order By: Relevance
“…Therefore, it was suggested that plain radiograph should not be taken as a routine CTS diagnostic tool unless hard tissue-related changes were suspected. Recent advances in imaging techniques in ultrasound and MRI, i.e., shear wave elastography [25], pressuremonitor elastography [26], diffusion tensor imaging of MRI [27], have been reported to be more beneficial in diagnosing neurological conditions of carpal tunnel syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was suggested that plain radiograph should not be taken as a routine CTS diagnostic tool unless hard tissue-related changes were suspected. Recent advances in imaging techniques in ultrasound and MRI, i.e., shear wave elastography [25], pressuremonitor elastography [26], diffusion tensor imaging of MRI [27], have been reported to be more beneficial in diagnosing neurological conditions of carpal tunnel syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the advancement of radiographic diagnosing has been progressing dramatically. The diffusion-weighted image (DWI) of MRI is able to capture edematous changes in brain and peripheral nerves 17) . The apparent diffusion coefficient could be an indicator when detecting damage of the nerve root, the amount of which increases at the lesion of angiogenic edema 18) .…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between median DTI metrics and electrophysiology for the carpal tunnel nerve has been reported, suggesting a role for DTI in the in vivo assessment of axon and myelin sheath integrity 7,[42][43][44] . According to a meta-analysis published in 2016 that included 316 patients and 293 healthy controls across 12 studies, fractional anisotropy of the median nerve was significantly lower in patients with CTS, and this measure enabled diagnosis of CTS with an overall sensitivity of 82.8% and a specificity of 77.8% 44 . Despite these encouraging preliminary results, DTI of peripheral nerve should still be considered experimental owing to the relatively small datasets in these studies and the variability of DTI thresholds across studies.…”
Section: Entrapment Neuropathiesmentioning
confidence: 95%